Penerapan Metode Least Square Dalam Memprediksi Penjualan Mie Instan - Siregar, Dodi; Irwanda, Fikri Dio; Dafitri, Haida (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Instant noodles are a food product made from wheat flour or wheat flour with or without the addition of other permitted food ingredients and additives. Instant noodles are popular because they taste delicious, are a practical way to cook and also have an affordable price. Instant noodles are one of the products that are often sold at Elvi stores. In fact, sales of instant noodle products at Elvi stores are erratic. This is because instant noodles are often an alternative food when people are reluctant to cook. The problem with Elvi's shop is that it cannot determine the stock of instant noodles to store which will then be sold more to the public. To minimize losses and maximize profits, a prediction system for instant noodle sales in the coming months is needed. The method used is the Least Square method which is processed based on sales trends. Based on the instant noodle prediction results using the Least Square method on sales data for the period January 2022 to August 2022, the prediction results achieved the highest accuracy of 99% and the lowest accuracy of 85%.